Bus driver accident record; stability over time, exposure and culpability - af Wåhlberg, Anders E.; Dorn, Lisa (Taylor & Francis, 2019)
The tendency for drivers to have a stable accident record over time was tested in a population of bus drivers. Analyses included investigations of the effects of responsibility for the crash, exposure and length of time period, on stability. All associations between numbers of accidents for individuals in different short time periods were found to be weak, but longer time periods increased the size of the correlations. Restricting the analyses to include only those crashes for which the drivers were deemed responsible had a slightly negative effect on correlations. However, this was due to lower means (and thus variance) in these calculations. Similarly, controlling for hours worked decreased the correlations somewhat, but this was due to an outlier problem. The results are consistent with previous research and indicate that stability of accident involvement exists and that the effects can be reliably found under certain methodological circumstances. The sizes of coefficients are determined mainly by the restriction of variance, not by any underlying lack of stability. The stable tendency to cause mishaps within the same environment is a strong factor in traffic safety although this is not apparent when variance in the data is low.
Keywords: bus driver; culpability; crash; traffic accident; exposure